2023
DOI: 10.1002/rcr2.1192
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilic pneumonia developed after dupilumab administration in a patient with atopic dermatitis

Abstract: A 63-year-old woman with refractory atopic dermatitis started treatment with dupilumab. She developed a cough 4 days later, sputum, and a slight fever 2 weeks later. Laboratory test results showed a blood eosinophil count of 7360/μL. Chest x-ray and computed tomography scan showed infiltrative shadows with surrounding consolidation of both upper lobes. Bronchoalveolar lavage fluid eosinophil count was increased (50.0%), and histopathological findings were consistent with numerous eosinophilic infiltrations. Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…A recognized side effect of dupilumab is transient eosinophilia, which typically improves spontaneously and thereafter remains asymptomatic in most cases. In contrast, fewer than 20 cases of dupilumab-induced eosinophilic pneumonia have been reported (2)(3)(4)(5)(6). We encountered a case in which eosinophilic pneumonia was initially suspected; however, bronchoscopy revealed that the patient had developed diffuse alveolar hemorrhage rather than eosinophilic pneumonia.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…A recognized side effect of dupilumab is transient eosinophilia, which typically improves spontaneously and thereafter remains asymptomatic in most cases. In contrast, fewer than 20 cases of dupilumab-induced eosinophilic pneumonia have been reported (2)(3)(4)(5)(6). We encountered a case in which eosinophilic pneumonia was initially suspected; however, bronchoscopy revealed that the patient had developed diffuse alveolar hemorrhage rather than eosinophilic pneumonia.…”
Section: Discussionmentioning
confidence: 79%
“…Clinical trials have shown that dupilumab can cause temporary peripheral blood eosinophilia without causing any problems. However, several cases of eosinophilic pneumonia associated with dupilumab have been reported (2)(3)(4)(5)(6). However, to date, no case of diffuse alveolar hemorrhage caused by dupilumab has previously been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have found that dupilumab can cause EP, while others have described EP treated with dupilumab. 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 The mechanisms underlying dupilumab‐induced EP remain unclear. However, previous reports of EP after dupilumab treatment suggest an association with hypereosinophilia.…”
Section: Discussionmentioning
confidence: 99%
“… 1 However, several reports have described dupilumab‐induced eosinophilic pneumonia (EP) after treatment with dupilumab (Table 1 ). 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 In most of those reports, dupilumab was discontinued and the patients were treated using prednisolone. Other reports have described the efficacy of dupilumab for chronic EP (CEP).…”
Section: Introductionmentioning
confidence: 99%